The Evolution of Talent Development Programs in Academic Literature: A Bibliometric Review - Mohammad Gifari Sono; Diputra, Gede Bagus Wira (The Eastasouth Management and Business, 2024)
This study conducts a comprehensive bibliometric analysis of the evolution of talent development research, mapping its key themes, influential authors, and geographic collaborations from 1952 to 2024. Using data from Google Scholar and VOSviewer, the analysis identifies central themes such as "development programs," "talent management," and "training," highlighting their sustained importance in both corporate and educational contexts. The study also reveals the increasing interdisciplinary nature of the field, with growing interest in youth sports and gifted education. Collaboration networks show the United States and United Kingdom as central hubs in global research, while countries like India and China are emerging contributors. However, geographic imbalances remain, particularly in regions like South America and Africa. The findings suggest future research opportunities in interdisciplinary approaches, the integration of emerging technologies, and expanding global collaboration. This study provides a roadmap for researchers and practitioners looking to understand and contribute to the future of talent development.